Current understanding of the inhibition factors and their mechanism of action for the lignocellulosic biomass hydrolysis - Agrawal, Ruchi; Verma, Amit; Singhania, Reeta Rani; Varjani, Sunita; Di Dong, Cheng; Kumar Patel, Anil (Bioresource technology, 2021)
Degradation products from lignocellulosic biomass under acidic pretreatment conditions. [Display omitted] •Revolution in inhibition reduction is prerequisite to improve hydrolysis efficiency.•Understanding inhibition mechanism would lead a process design to overcome it.•HSL would be cost-effective with intended lower inhibitors concentration.•Robust cellulolytic cocktail must be designed which could resist inhibitors.•Proposed ideas to alleviate enzyme inhibition and improve enzymatic hydrolysis. Biorefining of lignocellulosic biomass is a relatively new concept but it has strong potential to develop and partially replace the fossil derived fuels and myriad of value products to subsequently reduce the greenhouse gas emissions. However, the energy and cost intensive process of releasing the entrapped fermentable sugars is a major challenge for its commercialization. Various factors playing a detrimental role during enzymatic hydrolysis of biomass are inherent recalcitrance of lignocellulosic biomass, expensive enzymes, sub-optimal enzyme composition, lack of synergistic activity and enzyme inhibition caused by various inhibitors. The current study investigated the mechanism of enzyme inhibition during lignocellulosic biomass saccharification especially at high solid loadings. These inhibition factors are categorized into physio-chemical factors, water-soluble and -insoluble enzyme inhibitors, oligomers and enzyme-lignin binding. Furthermore, different approaches are proposed to alleviate the challenges and improve the enzymatic hydrolysis efficiency such as supplementation with surfactants, synergistic catalytic/non-catalytic proteins, and bioprocess modifications.